Kecerdasan Emosional Perawat dan Hubungannya dengan Kelengkapan Pengisian Asesmen Awal Pasien - Tonce Limbong; Netty Nursanty; Lusianawaty Lusianawaty; Sherly Wagiu; Dessy Aritonang; Nerista Barus; Eva Malinti; Jeanny Situmorang; Rodina Sinaga; Yanti Sagala (NUTRIX, 2023)
The emotional intelligence of nurses and their relationship with the completeness of filling out the patient's initial assessment, has been investigated and analyzed. The results and discussion are described in this paper. The emotional intelligence of nurses was measured using an emotional intelligence measurement instrument developed by Goleman, while the completeness of filling out the patient's initial assessment was measured using the patient's initial assessment instrument. A total of 50 nurses were used as participants. From the results of the analysis carried out on the data obtained, it was found that the emotional intelligence of nurses had a significant and strong relationship with the completeness of filling out the patient's initial assessment. The relationship is positive with a correlation coefficient of r = 0.896 (p = 0.01). Nurses as participants in this study have emotional intelligence with the strongest elements which are: (1) self-motivation, (2) emotional awareness, (3) empathy, (4) social relationships, and lastly (5) emotional control. Among this five elements, the greatest contributor to the formation is emotional awareness, followed by the element of empathy. The least contributors are the element of emotional control and the element of social relations. This is due to the fact that nurses have low emotional control and social relationships. Keywords: Emotional intelligence; Nurses; Completeness of filling; Initial assessment; Patient Abstrak Kecerdasan emosional perawat dan hubungannya dengan kelengkapan pengisian asesmen awal pasien, telah diselidiki dan dianalisis. Hasil dan pembahasannya diuraikan dalam makalah ini. Kecerdasan emosional perawat diukur menggunakan instrumen pengukuran kecerdasan emosional yang dikembangkan oleh Goleman, sedangkan kelengkapan pengisian asesmen awal pasien diukur menggunakan instrumen asesmen awal pasien. Sebanyak 50 perawat digunakan sebagai peserta. Dari hasil analisis yang dilakukan terhadap data yang diperoleh diperoleh bahwa kecerdasan emosional perawat mempunyai hubungan yang signifikan dan kuat dengan kelengkapan pengisian asesmen awal pasien. Hubungannya positif dengan koefisien korelasi r = 0,896 (p = 0,01). Perawat sebagai partisipan dalam penelitian ini memiliki kecerdasan emosional dengan unsur yang paling kuat yaitu: (1) motivasi diri, (2) kesadaran emosional, (3) empati, (4) hubungan sosial, dan terakhir (5) kontrol emosi. Diantara kelima unsur tersebut, yang paling besar penyumbang pembentukannya adalah kesadaran emosional, disusul unsur empati. Yang paling sedikit menyumbang adalah unsur pengendalian emosi dan unsur hubungan sosial. Hal ini disebabkan karena perawat mempunyai kontrol emosi dan hubungan sosial yang rendah. Kata Kunci: Kecerdasan emosional; Perawat; Kelengkapan pengisian; Penilaian awal; Pasien